Delirium: an interdisciplinary challenge - Fruehwald, T.; Weissenberger-Leduc, M.; Jagsch, C.; Singler, Katrin; Gurlit, S.; Hofmann, W.; Boehmdorfer, B.; Iglseder, B. (Zeitschrift für Gerontologie und Geriatrie, 2014)
Delirium, the acute deterioration of cognitive function and attention, is the most frequent mental disorder in elderly. Its correct diagnosis and adequate management are of crucial importance for the patient's health and functional outcome. First of all, one has to be aware of the possibilities of preventing this complex, potentially life-threatening problem, which means recognizing the patient at risk, avoiding environmental stress and causal factors (i.e., anticholinergic medication) in cognitively impaired patients, and timely reaction to prodromal symptoms. Causal therapy (i.e., treatment of the causal condition and/or eliminating the precipitating situation) is imperative. It must be accompanied by nursing and environmental measures and, if necessary, by antipsychotic and/or sedating symptomatic treatment.
EVALuna2:10543